«CITY OF BROKEN PROMISES» AS AN ETHNOGRAPHIC NOVEL: REPRESENTATIONS OF 18TH-CENTURY MACAO - Puga, Rogério Miguel (2019)
Using the concept of ethnographic novel, we analyse the historical novel City of Broken Promises (1967), by Austin Coates, and the way this narrative uses a number of anthropological and literary devices to represent the spaces and the everyday life of the several communities (English, Portuguese, Chinese) of seventeenth-century Macao.